Improving the Hydrogen-Adsorption Properties of a Hydroxy-Modified MIL-53(Al) Structural Analogue by Lithium Doping - Himsl, Dieter; Wallacher, Dirk; Hartmann, Martin (Angewandte Chemie International Edition, 2009)
Lithium makes the difference: A simple strategy for the synthesis of lithium-doped porous metal-organic frameworks (MOFs) is developed (see structure; C black, O red, AlO blue octahedra), thus paving the way for the facile preparation of lithium-doped MOFs. Moreover, the significant increase in hydrogen adsorption predicted by theoretical calculations is observed. © 2009 Wiley-VCH Verlag GmbH & Co. KGaA.
Keywords: Adsorption; Doping; Hydrogen; Lithium; Microporous materials